Rapunzel Syndrome: A Rare Presentation with Giant Gastric Ulcer - Antonios Athanasiou; Adamantios Michalinos; Demetrios Moris; Eleftherios Spartalis; Nikolaos Dimitrokallis; Vaios Kaminiotis; Demetrios Oikonomou; John Griniatsos; Evangelos Felekouras (Case Reports in Medicine)
The Rapunzel syndrome refers to an uncommon and rare form of trichobezoar that extends past the stomach into the small intestines. The Rapunzel syndrome is usually found in young female patients with a history of psychiatric disorders, mainly trichotillomania and trichophagia. We describe a case of Rapunzel syndrome in a 15-year-old girl who presented with abdominal pain, vomiting, and weight loss. We performed a surgical laparotomy and successfully removed a huge trichobezoar extending into the small intestine.